2020
DOI: 10.3390/ai1010003
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Lung Cancer Nodules Detection and Classification in CT Scans

Abstract: Detecting malignant lung nodules from computed tomography (CT) scans is a hard and time-consuming task for radiologists. To alleviate this burden, computer-aided diagnosis (CAD) systems have been proposed. In recent years, deep learning approaches have shown impressive results outperforming classical methods in various fields. Nowadays, researchers are trying different deep learning techniques to increase the performance of CAD systems in lung cancer screening with computed tomography. In this work, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 78 publications
0
51
0
1
Order By: Relevance
“…This issue has been tackled by applying data augmentation techniques. The most widely used are translations, rotations, resizing, flipping and cropping patches [ 34 ]. There have also been more sophisticated approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has been tackled by applying data augmentation techniques. The most widely used are translations, rotations, resizing, flipping and cropping patches [ 34 ]. There have also been more sophisticated approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, various authors have reported automatic lung nodule detection algorithms using deep learning 19 . In the effort to minimize false negatives and FPs, Wang et al proposed a nodule‐size‐adaptive model that can measure the nodule sizes, types, and locations from three‐dimensional (3D) images 20 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Meanwhile, various authors have reported automatic lung nodule detection algorithms using deep learning. 19 In the effort to minimize false negatives and FPs, Wang et al proposed a nodule-size-adaptive model that can measure the nodule sizes, types, and locations from three-dimensional (3D) images. 20 Moreover, Dou et al used 3D convolutional neural networks to extract multilevel contextual information to reduce FPs, 21 while Xie et al utilized two-dimensional (2D) convolutional neural networks for FP reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], Deep learning (DL) frameworks are used as they extract features deep down the hidden network with variable factors acquired during training. Most medical imaging models use Convolution Neural Networks (CNN) for prediction.…”
Section: Iintroductionmentioning
confidence: 99%